The role of fibrinolysis in the development of prediabetes-associated coronary heart disease: a focus on the plasminogen activator inhibitor -1 and its potential use as a predictive marker in diet-induced prediabetes - Gumede, Nompumelelo; Khathi, Andile (Frontiers in Nutrition, 2023)
Introduction: Type 2 diabetes mellitus (T2DM) is preceded by prediabetes, which is associated with sedentary lifestyles and consumption of high-calorie diets. Studies have shown that impaired glucose homeostasis creates an environment for developing T2DM-related complications. Using a high-fat-high-carbohydrate diet-induced prediabetes animal model, this study sought to assess the risk factors of coronary heart disease (CHD) in diet-induced prediabetes and identify biomarkers that can be used for early detection of prediabetes-associated CHD. Methods: Male Sprague Dawley rats were randomly grouped into two groups and were kept on different diets for 20 weeks (n=6 in each group). One group was fed standard rat chow to serve as a non-prediabetes (NPD) control, while the other group consumed a high-fat-high-carbohydrate diet to induce prediabetes (PD). Post induction, the homeostasis model assessment-insulin resistance (HOMA-IR) and glycated haemoglobin (HbA1c) was used to test for insulin resistance. Body weight, mean arterial pressure (MAP), resting heart rate (HR), inflammatory cytokines (C-reactive protein (CRP), tumor necrosis factor (TNF-α), interleukin-6 (IL-6)), lipids (total cholesterol (TC), triglyceride (TG), lipoproteins (HDL, LDL, VLDL)), endothelial function (endothelial nitric oxide (eNOS), endothelin -1 (ET-1)), fibrinolysis (plasminogen activator inhibitor-1 (PAI-1)) were all measured to assess the risk of CHD. All data were expressed as means ± S.E.M. Statistical comparisons were performed with Graph Pad.Instat Software using Student's two-sided t-test. Correlation coefficient and linear regression were calculated to assess the association. The value of p< 0.05 was considered statistically significant. Results: There was significant insulin resistance accompanied by significantly increased HbA1c and body weight in PD compared to NPD. Simultaneously, there was a significant increase in inflammatory cytokines in PD compared to NPD. This was accompanied by significantly increased TG and VLDL and endothelial dysfunction in PD. The association between HOMA-IR and PAI-1 was insignificantly positive in NPD, whereas a significantly strong positive association was observed in PD.There is a positive correlation between insulin resistance and PAI-1 during prediabetes; therefore, suggesting that prediabetes increases the risk of developing vascular thrombosis. The current therefore study warrants further investigation on PAI-1 and other markers of fibrinolysis for the early detection of thrombosis and risk of CHD in prediabetes.